Epstein-Barr Virus (EBV) detection and typing by PCR: a contribution to diagnostic screening of EBV-positive Burkitt's lymphoma - Hassan, Rocio; White, Lidia Roxana; Stefanoff, Claudio Gustavo; Oliveira, Deilson Elgui de [UNESP]; Felisbino, Fabricio E.; Klumb, Claudete Esteves; Bacchi, Carlos E. [UNESP]; Seuanez, Hector N.; Zalcberg, Ilana R. (Biomed Central Ltd., 2006)
Background: Epstein-Barr virus (EBV) is associated to the etio-pathogenesis of an increasing number of tumors. Detection of EBV in pathology samples is relevant since its high prevalence in some cancers makes the virus a promising target of specific therapies. RNA in situ hybridization (RISH) is the standard diagnostic procedure, while polymerase chain reaction (PCR)-based methods are used for strain (EBV type-1 or 2) distinction. We performed a systematic comparison between RISH and PCR for EBV detection, in a group of childhood B-cell Non-Hodgkin lymphomas (NHL), aiming to validate PCR as a first, rapid method for the diagnosis of EBV-associated B-cell NHL.Methods: EBV infection was investigated in formalin fixed paraffin- embedded tumor samples of 41 children with B-cell NHL, including 35 Burkitt's lymphoma (BL), from Rio de Janeiro, Brazil, by in situ hybridization of EBV-encoded small RNA (EBER-RISH) and PCR assays based on EBNA2 amplification.Results: EBV genomes were detected in 68% of all NHL. Type 1 and 2 accounted for 80% and 20% of EBV infection, respectively. PCR and RISH were highly concordant (95%), as well as single- and nested-PCR results, allowing the use of a single PCR round for diagnostic purposes. PCR assays showed a sensitivity and specificity of 96% and 100%, respectively, with a detection level of 1 EBV genome in 5,000-10,000 EBV-negative cells, excluding the possibility of detecting low-number EBV-bearing memory cells.Conclusion: We describe adequate PCR conditions with similar sensitivity and reliability to RISH, to be used for EBV diagnostic screening in high grade B-NHL, in at risk geographic regions.